THE MOQI AND USE OF SOCIAL WORKERS WITHIN AN INTERDISCIPLINARY TEAM TO REDUCE UNNECESSARY HOSPITALIZATIONS. (11th November 2018) - Galambos, C; Pritchett, A; Rantz, M
Abstract: The Missouri Quality Initiative's (MOQI) aim to reduce potentially avoidable hospitalizations among long stay nursing facility residents was achieved through: (1) condition management; (2) early illness detection; (3) use of INTERACT and Quality Improvement; (4) end-of-life and care transitions discussions; (5) improved communication using health information technology. Advanced Practice Registered Nurses (APRN's) were embedded in each facility supported by a team including a master's prepared social work care transitions coach (CTC). The MOQI achieved a 40% reduction in all cause hospitalizations and a 57.7% reduction in potentially avoidable hospitalizations (p=001); all cause visits were reduced by 54.1%, and potentially avoidable ED visits reduced by 65.3% (p=0.001). Highlights of the model and use of the CTC, discussion of results, integration of social service departments, and implications for practice will be presented.